The Effect Of Attitude Towards Sustainable Business Models, Social Norms And Perceived Behavioral Control On Behavioral Intention To Adopt It With Open Innovation Ecosystem Partnership As An Intervening Variable : (A Case Study On Cobek Batu Merapi Business) - Pamungkas, Aldian Sidha; Hasin, Al (International Journal of Business and Quality Research, 2025)
This study aims to analyze the influence of attitudes towards sustainable business models, social norms, and perceived behavioral control on the behavioral intentions of MSMEs in adopting sustainable business models, with open innovation ecosystem partnerships as an intervening variable. The object of the study focused on the Karya Batu Indah MSME, namely Cobek Batu Merapi craftsmen who have the potential to develop their business through the application of sustainability principles. Respondents in this study numbered 110 people, with the following criteria: being an active business actor in the Karya Batu Indah MSME, having run the business for at least one year, having a role in business decision-making, and being willing and able to provide information needed in the study. Data collection was carried out using a five-point Likert scale questionnaire, then the data were analyzed using the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method through SmartPLS 3.0 software. The results showed that social norms have a significant positive influence on open innovation ecosystem partnerships, as well as contributing to attitudes and perceived behavioral control. Furthermore, open innovation ecosystem partnerships and perceived behavioral control were shown to have a significant positive influence on the behavioral intentions of MSMEs in adopting sustainable business models. Attitudes toward sustainable business models also positively influence behavioral intentions. The conclusion of this study is that the adoption of sustainable business models in the Cobek Batu Merapi MSME industry is more determined by social support and the business owner's ability to manage sustainability practices than by individual attitudes alone. Therefore, building a partnership ecosystem that supports open innovation and strengthens social norms is key to increasing MSME commitment to sustainability.